Mengintegrasikan Seni Dan Sains Dalam Strategi Pembelajaran Interdisipliner - Salmawati Salmawati (Jurnal Sultra Elementary School, 2024)
Integration of arts and science in interdisciplinary learning provides a holistic approach to developing students' cognitive, creative, and affective abilities. This article aims to examine various strategies used in combining arts and science in educational contexts. Literature studies show that this approach is able to increase student engagement, foster creativity, and strengthen understanding of scientific concepts. Project-based learning models and multidisciplinary collaboration are the keys to success in integrating arts and science.